The line Rico is the earliest maturing accession in the VIR collection of spring bread wheat - B. V. Rigin; E. V. Zuev; A. S. Andreeva; Z. S. Pyzhenkova; I. I. Matvienko (Труды по прикладной ботанике, генетике и селекции)
Background. To optimize the process of bread wheat breeding for earliness and environmental adaptability, searching for new source material is a crucial task. The ultra-early line Rico (k-65588) – Triticum aestivum var. erythrospermum Koern. – stands out among the bread wheat accessions from the VIR collection for its important adaptive features.Materials and methods. Spring wheat accessions with different speed of development were selected from the VIR collection for this study, along with the ultra-early lines Rifor 1 ... 10 (F6-7 Rico × Forlani Roberto k-42641) and Fori 1 ... 8 (k-65589 ... k-65596) (F4 Foton k-55696 × Rico). Their responses to a short 12-hour day were assessed. Vernalization conditions were 30 days at 3°C. The genetics of plant sensitivity to vernalization and photoperiods was studied using allele-specific primers for the genes Vrn-A1, Vrn-B1, Vrn-D1 and Ppd-D1.Results and conclusions. In the Northwest of Russia, the period from seeding to heading for Rico plants was 39.9 ± 1.49 days, or 14.8 ± 1.22 days less than for the released commercial wheat cultivars. Among the 8400 wheat accessions, studied by the Wheat Genetic Resources Department of VIR in this area from 1948 to 2018, the shortest period from germination to heading was observed in the line Rico: 29 (28–30) days. The absence of response to vernalization in Rico, Fori and Rifor lines was determined by the dominant alleles Vrn-A1, Vrn-B1 and Vrn-D1. Photoperiodism in Rico and partially in Rifor was controlled by at least two genes: Ppd-D1 and Ppd-B1. In the F2 population of Rico hybrids with 8 wheat accessions no transgression was observed beyond the limits of Rico‘s variation. The difference in the development rate between Rico and other wheat accessions is controlled by two or three non-allelic genes. Rifor lines can compete in productivity with commercialized wheat cultivars.